Analisis Pengaruh Kompensasi Dan Budaya Organisasi Terhadap Kinerja Pemerintah Daerah Studi Empiris Pada Dinas Pemuda, Olahraga, Kebudayaan, Dan Pariwisata Kabupaten Banyumas - Andhika tegar, Cakra Pratama (2016)
this research aimed at knowing the influence of compensation on the official's performance in the regional government of Banyumas Regency and to know the influence of organizational culture on the official's performance in the regional government of Banyumas population in this research was the official's in the government of Banyumas Regency and sample in this reseacrh were the official's of the regional government of Banyumas Regency, meanwhile the sample technique in this research was through the approach of non probability sampling method that was purposive sampling with the criteria as follows: the official's who have worked for minimally one year and the officials who have been the civil servants based on the result of the research, the compensation had significant influence on the officials performance of the department of youth, sport, culture, tourism of Banyumas Regency. the organizational culture had significant influence on the officials performance of the department of youth, sport, culture, and tourism of Banyumas Regency. and from the result of the analysis collectively, the variabels of compensation an the organizational culture had an influence on the officials performance of the department of youth, sport, culture, and tourism of Banyumas Regency